Efektivitas Implementasi Program Keluarga Harapan (PKH) Dalam Upaya Penanggulangan Kemiskinan (Studi Pada Dinas Sosial Kabupaten Blitar) - Anwar Hakim Darajat; Septa Ekasari (Universitas Islam Balitar, 2021)
Effectiveness in general states the extent to which a goal has been achieved whose initial process is determined by the target. Measuring the level of effectiveness is done by comparing the determined plan with the tangible results that are realized. Various efforts have been made by the Government of Indonesia to overcome various problems of poverty, one of which is through the Program Keluarga Harapan (PKH). Keluarga Penerima Manfaat (KPM) as one of the recipients of the conditional social assistance program who are designated as beneficiaries of the Program Keluarga Harapan (PKH). The purpose of this study was to determine the effectiveness of the implementation of the Program Keluarga Harapan (PKH) in poverty reduction efforts and to find out the constraints of the Program Keluarga Harapan (PKH) in poverty reduction efforts. The research method used a qualitative descriptive. The results show that the effectiveness of the implementation of the Program Keluarga Harapan (PKH) can be said to be effective in poverty reduction efforts seen from several indicators of effectiveness, but there are still some obstacles including losing ATMs, understanding of socialization that is still not accepted, the difference in understanding between stakeholders and the difficult terrain. Suggestions provide re-socialization of the Program Keluarga Harapan (PKH) to stakeholders so that the Program Keluarga Harapan (PKH) can be right on target to the community and repair difficult terrain so that difficult areas can be reached.